Guidelines for Using Online Social Network in a Studio Art Program of Undergraduate Students - Pratoom, Natthakan; Prompan, Inthira (An Online Journal of Education, 2021)
The objective of this study was to propose guidelines for using appropriate social network to facilitate studio art program. The samples of this study were consisted of 22 studio art teachers and 360 students from 8 universities, which were Chulalongkorn University, Srinakharinwirot University, Chiang Mai University, Khon Kaen University, Burapha University, Prince of Songkla University, Ramkhamhaeng University, and Bansomdejchaopraya Rajabhat University. The instruments used in this study were interview form, questionnaire, and observation form. The quantitative data was analysed by calculating percentage, mean, and standard deviation. The interview and observation data were analysed by using content analysis. The results showed that integrating social network into studio art program increased class learning efficiency, minimized time and space limitation, increased student learning and research channel, and encouraging idea and development. 1) For develop craft, the most appropriate social network is content community. 2) For engage & persist, the most appropriate type of social network is social networking site or SNS. 3) Every type of social network can be used to develop envision and inspiration. 4) To express the idea and expression, the most appropriate type of social network is SNS. 5) To observe, the most appropriate social network is SNS 6) Blog is the most appropriate type for stretch & explore. And 7) to understand art world, Blog is the most appropriate type of social network. Teachers have the very important roles in advising student how to learn, research, and using social network appropriately.